Pengaruh Literasi Keuangan dan Inklusi Keuangan terhadap Kinerja IKM Batik di Kabupaten Jombang - Nurfaizah, Nadia Martha; Qomariyah, Siti Nur (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the influence of financial literacy and financial inclusion on the performance of Batik Small and Medium Industries (SMEs) in Jombang Regency using a quantitative approach through the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The study population includes all Batik SMEs in Jombang Regency, totaling 25 business units, so the sampling technique used is a census. Data were collected through a structured questionnaire that measures the level of financial literacy, financial inclusion, and business performance, then analyzed to determine the causal relationship between variables. The results of partial hypothesis testing indicate that financial literacy does not have a significant effect on the performance of Batik SMEs with a P-Value of 0.097, while financial inclusion also does not show a significant effect with a P-Value of 0.293 (both > 0.05). These findings indicate that financial knowledge and access to formal financial services owned by business actors have not been able to directly improve business performance.  However, the results of simultaneous testing show an R-Square value of 0.528, which means that financial literacy and financial inclusion together are able to explain 52.8% of the variation in the performance of Batik SMEs, so that the model has moderate explanatory power. The insignificance of the partial effect indicates a gap between knowledge and financial access with actual application in business financial management, so that application assistance, practical financial management training, and strengthening of managerial competencies are needed to improve the performance of Batik SMEs sustainably.